Question
3. Solve. \begin{tabular}{|l}\hline a. 10 tens -1 ten 1 tenth \\ b. \end{tabular}
Ask by Todd Donnelly. in the United States
Feb 13,2025
Real Tutor Solution
Tutor-Verified Answer
Answer
The result is 90.1.
Solution
Let's solve the problem step by step.
### Part a: 10 tens - 1 ten + 1 tenth
1. **Convert the terms to a common unit:**
- 10 tens = \(10 \times 10 = 100\)
- 1 ten = \(1 \times 10 = 10\)
- 1 tenth = \(0.1\)
2. **Substitute the values into the expression:**
\[
100 - 10 + 0.1
\]
3. **Perform the calculations step by step:**
- First, subtract 10 from 100:
\[
100 - 10 = 90
\]
- Then, add 0.1 to 90:
\[
90 + 0.1 = 90.1
\]
### Final Answer for Part a:
The result of \(10 \text{ tens} - 1 \text{ ten} + 1 \text{ tenth}\) is \(90.1\).
If you have any further parts or questions, please let me know!
Reviewed and approved by the UpStudy tutoring team
Like
error msg
![](/pmw/light_bulb.png?etag=525fd69ac661e11754e2fc9f1b18a4ee)
![](/pmw/spiral_notepad.png?etag=abe3906b7558c543a7b30ba53a3b5a5b)
Mind Expander
To solve part a, let's break it down! You start with 10 tens, which equals 100. Then, you subtract 1 ten, which is 10. So you have 100 - 10 = 90. Now, adding the 1 tenth (which is 0.1) gives you 90 + 0.1 = 90.1. For part b, if you have a similar set of operations, just keep in mind to line up your values according to their place value (hundreds, tens, and tenths) for accurate calculations. This ensures you don't lose track of the values involved!